2012
DOI: 10.1016/j.humpath.2012.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Pericytoma with t(7;12) and ACTB-GLI1 fusion arising in bone

Abstract: Cytogenetic analysis of a primary bone neoplasm with pericytic features in a 67 year-old-male revealed a t(7;12)(p22;q13) among other karyotypic abnormalities. Subsequent molecular studies confirmed the presence of an associated ACTB-GLI1 fusion transcript. An identical 7;12 translocation is known to characterize a discrete group of soft tissue tumors belonging to the myopericytic category termed “pericytoma with t(7;12).” To the best of our knowledge, this is the first case of pericytoma with t(7;12) arising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 13 publications
0
48
0
Order By: Relevance
“…Myopericytoma shows variable cellularity and a collagenous or sometimes myxoid stroma, and may also show bulging subendothelial proliferation of tumor cells within vessels walls. Consistent genetic alterations have not been identified in myopericytoma, apart from a unique variant characterized by translocation t(7; 12)(p22; q13) which results in ACTB-GLI1 fusion [30][31][32] and a report of BRAF V600E mutations in a subset of myopericytomas [33]. Similar to a prior report [34], nuclear b-catenin expression is consistently absent in myofibroma and is useful in the distinction between sinonasal HPC and myopericytoma.…”
Section: Discussionmentioning
confidence: 53%
“…Myopericytoma shows variable cellularity and a collagenous or sometimes myxoid stroma, and may also show bulging subendothelial proliferation of tumor cells within vessels walls. Consistent genetic alterations have not been identified in myopericytoma, apart from a unique variant characterized by translocation t(7; 12)(p22; q13) which results in ACTB-GLI1 fusion [30][31][32] and a report of BRAF V600E mutations in a subset of myopericytomas [33]. Similar to a prior report [34], nuclear b-catenin expression is consistently absent in myofibroma and is useful in the distinction between sinonasal HPC and myopericytoma.…”
Section: Discussionmentioning
confidence: 53%
“…G-banding analysis of short-term cultured cells from the tumor yielded the karyotype 46,XX,der(7)t(7;12)(p22;q13), der(12)t(1;12)(q12;q13) [11]/46,idem,tas(X;8)(q28;q24) [3]/46, idem,tas(8;12)(q24;q24) [2] (Figure 2). FISH analysis using the CHOP break-apart probe ( Figure 3A and B) showed that the distal part of the probe (green signal) hybridized to the der(7)t(7;12)(p22;q13), whereas the proximal part of the probe (red signal) hybridized to der(12)t(1;12)(q12;q13) ( Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…This translocation resulted in an Actin beta 1 ( ACTB1 ) –GLI-1 fusion. Subsequently, more such cases were described and initially these unique tumours were construed as benign 7 8. However, the study by Antonescu and colleagues showed that these tumours indeed do have malignant potential 9.…”
Section: Introductionmentioning
confidence: 99%